Capacitación virtual para fomentar los hábitos de higiene en los niños de la Escuela Rafael Morán Valverde, Montalvo 2020-2021 - Garcés Valle, Juana Inés (2022)
This project deals with the development and implementation of a "Virtual Training Plan to promote Hygiene habits in the children of the Rafael Moran Valverde School, Montalvo 2020 - 2021" which allowed and provided a learning method that benefits students. students of the school, based on a total population of 91 parents. The research is of an applied type, having a mixed approach, and its scope is descriptive, in order to be able to solve the problem presented in the investigative work, it should be mentioned that the technique that was applied for data collection was the survey. Through the use of a questionnaire, this was sent through a WhatsApp link to the parents, guiding them to a Google platform, which contained the questions to be answered according to their criteria. The questionnaire consists of 20 questions with optional answers based on the LIKERT scale, once the results were obtained, statistical techniques such as hypothesis and chi square tests were applied, through research it was possible to conclude that the application of a virtual training plan on hygiene habits is very relevant in school children, because the good use of these habits help prevent contagious diseases, in addition to providing them with a good presentation at school or in any another place.